1977
DOI: 10.1111/j.1749-6632.1977.tb39735.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Olfactory System Modulate Affective Behavior in the Pigeon?*

Abstract: On the basis of his knowledge of the patterns of evolutionary development of the olfactory system and other forebrain structures, Herrick' proposed that the olfactory cortex served an activating function for "all cortical activities." In recent years, without addressing Herrick's proposal directly, several investigators have provided evidence that is pertinent to it. In an extensive review of this topic, Wenzell concluded that a number of behaviors are altered by a greatly diminished olfactory input and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…An activating effect of odors is supported by recent neurobiological studies which indicated an activation of neurons in the hippocampal formation and of the navigation circuity by lateralized activation of neurons in the piriform cortex (Jorge et al, 2014(Jorge et al, , 2016. However, some older findings could also be interpreted in view of an activating role of odors, as they revealed effects of olfactory deprivation on tasks not involving odors, such as tonic immobility and optokinetic nystagmus (rhythmic movements) (Wenzel and Rausch, 1977;Dornfeld and Bilo, 1990) as well as responses to visual stimuli (Wenzel and Salzman, 1968). Even the strongly disruptive effect of irregularly changing magnetic fields on pigeon orientation was suppressed in birds that had been deprived of odors by being kept in purified air during its application (Wallraff et al, 1986).…”
Section: Activating the Integration Of Local Factors Into The Navigatmentioning
confidence: 91%
“…An activating effect of odors is supported by recent neurobiological studies which indicated an activation of neurons in the hippocampal formation and of the navigation circuity by lateralized activation of neurons in the piriform cortex (Jorge et al, 2014(Jorge et al, , 2016. However, some older findings could also be interpreted in view of an activating role of odors, as they revealed effects of olfactory deprivation on tasks not involving odors, such as tonic immobility and optokinetic nystagmus (rhythmic movements) (Wenzel and Rausch, 1977;Dornfeld and Bilo, 1990) as well as responses to visual stimuli (Wenzel and Salzman, 1968). Even the strongly disruptive effect of irregularly changing magnetic fields on pigeon orientation was suppressed in birds that had been deprived of odors by being kept in purified air during its application (Wallraff et al, 1986).…”
Section: Activating the Integration Of Local Factors Into The Navigatmentioning
confidence: 91%
“…In several experiments, Wenzel and collaborators were able to demonstrate, by a lesion approach, these non-olfactory functions of the olfactory pathway. After lesions of the olfactory nerves and/or bulbs, performance was significantly decreased in learning situations [48, 112] and changes in tonic immobility, aggression [114] and reactivity in new situations [115] were also detected.…”
Section: The Role Of Olfaction In the Control Of Reproductionmentioning
confidence: 99%
“…However, it is known that, besides their role in the perception of olfactory stimuli, olfactory bulbs play a relatively complex role in behavioral arousal. The behavioral deficits observed following olfactory nerves sections (which results in a retrograde degeneration of the olfactory bulbs) could thus have been related to general effects on arousal independently of the perception of olfactory stimuli (Kenshalo and Isaac 1977) as observed repeatedly in behavioral studies of birds (Wenzel and Salzman 1968; Wenzel et al 1969; Hutton et al 1974; Wenzel and Rausch 1977). Available data do not permit to discriminate between these two interpretations but the second one appears, at present, less likely because other behaviors that are not directly linked to copulations such as aggressive behaviors were not affected (Fig.…”
Section: Olfactory Communication During Social Interactions In Birdsmentioning
confidence: 97%